2007
DOI: 10.1111/j.1365-2567.2007.02661.x
|View full text |Cite
|
Sign up to set email alerts
|

Malaria protection in β2‐microglobulin‐deficient mice lacking major histocompatibility complex class I antigens: essential role of innate immunity, including γδT cells

Abstract: It is still controversial whether malaria protection is mediated by conventional immunity associated with T and B cells or by innate immunity associated with extrathymic T cells and autoantibody-producing B cells. Given this situation, it is important to examine the mechanism of malaria protection in b 2 -microglobulin-deficient (b 2 m(-/-)) mice. These mice lack major histocompatibility complex class I and CD1d antigens, which results in the absence of CD8 + T cells and natural killer T (NKT) cells. When C57B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
1
12
1
1
Order By: Relevance
“…There were no significant differences in serum cytokine levels, including IFN-␥, between MAb-treated and control mice. Our results agree with those of others who observed that the depletion of splenic cells with anti-NK1.1 MAb does not alter the time course of P. chabaudi parasitemia (19,41,53).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…There were no significant differences in serum cytokine levels, including IFN-␥, between MAb-treated and control mice. Our results agree with those of others who observed that the depletion of splenic cells with anti-NK1.1 MAb does not alter the time course of P. chabaudi parasitemia (19,41,53).…”
Section: Discussionsupporting
confidence: 83%
“…NK cells in collaboration with dendritic cells are responsible for optimal IFN-␥ production dependent upon IL-12 (17,36,39,40). In contrast to the findings of Mohan et al, other studies indicate similar P. chabaudi parasitemia in depleted mice and intact controls after NK1.1 MAb depletion of NK cells (19,41,53). Using microarray analysis of blood cells from P. chabaudi-infected mice, Kim et al (18) reported a rapid production of IFN-␥ and activation of IFN-␥-mediated signaling pathways as early as 8 h after infection; however, NK cells did not express IFN-␥ or exhibit IFN-␥-mediated pathways in their analysis.…”
contrasting
confidence: 52%
“…This study showed that vaccination of mice with recombinant poxviruses, fowl pox and modified vaccinia Ankara (MVA) expressing a P. berghei CS protein, induced activation of both iNKT cells and NK cells in the liver of BALB/c mice, while inducing CS-specific CD8+ T cells secreting both IFN-γ and TNF-α. In this study, it was observed that when iNKT-deficient mice were vaccinated with the poxviruses, the number of double cytokine producing, CS-specific CD8+ T cells slightly decreased, with similar levels of anti-malarial protection at relatively early time points after vaccination [35]. However, at later time points after vaccination, a slightly better rate of protection was observed in V 14NKT-deficient mice compared to wild-type mice.…”
Section: Nkt Cells In Malariamentioning
confidence: 97%
“…However, the same group has later shown that the course of blood stage infection with P. yoelii was not significantly different between β2-microglobulin-deficient mice that also lack CD1d and wild-type control mice [35], suggesting the dispensable role of NKT cells. Although it is unclear why the two studies done by the same group resulted in different outcomes, in view of the great variability of the course of blood stage infection amongst individual mice, as determined by parasitemia, the mere prolongation, i.e.…”
Section: Nkt Cells In Malariamentioning
confidence: 99%
“…Confirmando o papel secundário das células T CD4 + não-convencionais nos camundongos resistentes à infecção pelo P. chabaudi, a contribuição das células T CD4 + não-convencionais é modesta e limitada ao segundo pico de parasitemia. Colaborando com estes resultados, na infecção pelo P. yoelii, a ausência das células T CD4 + restritas por CD1d promove um aumento na parasitemia na fase crônica da infecção (quarta semana), aumento não visto na fase aguda (129), contudo a aquisição de imunidade protetora não foi afetada (160).…”
Section: Figura 18: Modelo Para a Resposta Das Células T Cd4unclassified